Carbohydrate 3′-sialyllactose as a novel target for theranostics in pancreatic ductal adenocarcinoma - Kiyoshi Higashi; Keiko Maeda; Kaori Miyata; Saori Yoshimura; Keita Yamada; Daijiro Konno; Taro Tachibana; Koichi Saito (Tumor Biology, 2020)
We previously demonstrated that the carbohydrate 3′-sialyllactose is overexpressed in cancer stem-like cells such as metastatic pancreatic and poorly differentiated gastric cancer cells, and undifferentiated human embryonic stem cells. In this study, we investigated the possibility of 3′-sialyllactose as a target for theranostics in cancers using a recombinant mouse monoclonal antibody r3B1E2 that binds to 3′-sialyllactose. Immunohistochemistry analysis confirmed an elevated expression of 3′-sialyllactose in tumors of pancreas, stomach, and testis, while no expression of 3′-sialyllactose was observed in corresponding normal controls. In addition, a stage-independent expression of 3′-sialyllactose was observed, especially in pancreatic ductal adenocarcinoma (PDAC). The level of serum 3′-sialyllactose in PDAC subjects was significantly higher than that in healthy controls, providing excellent AUC of 0.88. We next explored the therapeutic potential of r3B1E2 for PDAC in vitro . Treatment of r3B1E2 with 3′-sialyllactose-bearing human PDAC cells exhibited a complement-dependent cytotoxicity, whereas no significant activity of r3B1E2 against 3′-sialyllactose-negative cells was observed. Collectively, these findings raise the possibility of 3′-sialyllactose as a novel target for theranostics in PDAC.